PENGARUH AKTIVITAS MAHASISWA KATOLIK TERHADAP PERKEMBANGAN IMAN DI LINGKUNGAN KAMPUS POLITEKNIK NEGERI MALANG - Pius, Intan Sakti; Kurniawan, Firman; Marcel, Francisco; Pasaribu, Roni Marciano; Mario, Kelvin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2023)
Catholic students are members in the campus environment who have a very important role, because mostCatholic students are young people. Catholic students believe that the Catholic faith is an inspiration in the process of human life. Catholic students can be successors in the campus environment, the future of the campus. Catholic students have an activity such as: training, education, renewal, worship, retreats, memoirs, youth Eucharist and activities. The type of research used in this study is quantitative research with a descriptive approach. Quantitative research methods are a type of research that has a systematic, planned, and well-structured approach to creating a research plan from start to finish. Respondents from Class 19 amounted to 45 students with a percentage of participating in off-campus activities by 15%, while respondents from Class 20 amounted to 31 students with a percentage of participating in off-campus activities by 5% and respondents from Class 21 amounted to 41 students with a percentage of participating in off-campus activities by 4%. The respondents of Class 19 were 45 students with a percentage of participating in campus activities at 5%, while the respondents of Class 20 were 31 students with a percentage of participating in campus activities at 7% and the respondents of Class 21 were 41 students with a percentage of participating in off-campus activities at 9%. From the above data it can be concluded that Catholic students have an important role in religious participation in increasing faith. It can be seen from the data above that they still have a fairly high sense of empathy in the presence of off-campus compared to inside the campus also has an influence in the activities carried out.Keywords: Catholic Youth, Faith and activities